Learning in Non-School Settings: Assessing the Roles of Zoos in Science Education - Copeland Solas, Eddia P. (Journal of Teaching and Learning, 2025)
This paper conducts a comprehensive review of the existing literature to examine the significance of zoos in cultivating scientific literacy in society. It focuses on revealing how educators can strategically utilize zoos as a valuable resource to encourage critical thinking about the nature of science (NOS) and socio-scientific issues (SSI) within the framework of formal school science curricula. This review encompasses the diverse educational initiatives zoos undertake, ranging from interactive exhibits to specialized programs, and explores their potential impact on enhancing student understanding of scientific concepts. Drawing on these findings, this paper provides recommendations for educators seeking to integrate zoo experiences into their teaching methodologies, emphasizing the potential for zoos to serve as dynamic platforms for fostering a more profound engagement with science. This research aims to provide practical insights that empower educators to leverage zoos to inspire critical thinking and scientific literacy within the broader community by bridging the gap between informal and formal learning environments.